The Role of Digital Literacy in Shaping Students' Perceptions of Exaggerated Claims in Skincare Advertisements - Sabrina Wandani Hutabarat; Mesra Sinambela; Rita Hartati (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This study aims to investigate the role of digital literacy in helping students assess the validity of skincare product advertisement claims, particularly exaggerated or hyperbolic claims often found in beauty product advertisements on social media. Using a qualitative approach with a cross-sectional survey design, this study involved 30 students of the English Literature Study Program at Medan State University as respondents who had basic knowledge of digital literacy and familiarity with skincare product advertisements. Data were collected through an online survey using a Likert scale to measure students' perceptions of advertising claims and the influence of digital literacy in evaluating those claims. The results showed that the majority of respondents had the ability to distinguish between valid and invalid claims thanks to their digital literacy. In addition, most students use the internet as the main source to verify advertising claims. However, there are still a small number of students who have not utilized digital literacy optimally. Overall, this study confirms the importance of digital literacy in helping students develop a critical attitude towards advertisements and can play a role in encouraging them to become smarter consumers who are skeptical of unrealistic claims in beauty product advertisements.